Using Habib Jafar Podcast as Islamic Information Media - Annisa Eka Syafrina (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to determine how to use Habib Jafar podcasts as a medium of Islamic information among a society. By using qualitative research methods with descriptive types, researchers conducted interviews with informants related to the research.The results show that the existing technology makes it easier for people to find information, especially religious information. Currently, people use podcasts, especially the Habib Jafar podcast as a medium for seeking Islamic information Just like other media, the use of podcasts brings positive and negative impacts for its users. but society must still be able to sort out the information that will be absorbed from the use of podcasts.